Pengaruh Pelatihan Ketrampilan Ekonomi Kreatif Dalam Merangsang Kreatifitas Wirausaha Terhadap Peningkatan Pendapatan Di Sentul Lio Desa Cisait Kabupaten Serang - Yulaikah, Yulaikah; Azizi, Enji; Respatiningsih, Inneke; Nurliana, Lia; Trikawati, Trikawati (LPPM Universitas Banten jaya, 2024)
This study aims to determine how much influence creative economy training, creativity of citizen entrepreneurs on increasing income. Based on the results of the hypothesis tested the influence of creative economy training, creativity of citizen entrepreneurs on increasing income is accepted. This has been proven from the results of simple linear regression tests which show that creative economy training, creativity of citizen entrepreneurs on increasing income are strong. It can be understood that the creative economy in Sentul Lio village, Cisait village, is engaged in the creative industry business sector, still lacking new innovations, creativity and new discoveries, so that it can compete with market developments. In fact, the creative economy will slowly replace the role of commodities and natural resources as supporters of the Indonesian economy. This study shows the results that there is an influence of creative economy training, creativity of citizen entrepreneurs on increasing income Keywords: Creative Economy Skills Training, Creativity of Citizen Entrepreneurs, increasing incomehttps://drive.google.com/file/d/1tazKq_d-eoV_uz7Gu29bPJc6MSgLd8Ic/view?usp=sharing